Inorganic wavelength plate and manufacturing method thereof

By leveraging the interaction between polymers and metal oxide precursors, inorganic wavelength plates with excellent heat resistance and durability are manufactured, solving the problem of insufficient heat resistance in polymer film wavelength plates. This enables high-yield micro-patterning and stable phase difference, making them suitable for high-performance electronic devices.

CN121703975APending Publication Date: 2026-03-20DEXERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511873192.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-05-10
Filing Date
2019-05-07
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing polymer film wavelength plates lack sufficient heat resistance and durability, making it difficult to meet the needs of high-density, highly integrated electronic devices. Furthermore, it is difficult to manufacture structural birefringent wavelength plates with fine patterns.

Method used

By using the interaction of a polymer with repeating units containing carbonyl groups and a metal oxide precursor, an inorganic wavelength plate with a wire grid structure is manufactured through polymer lattice formation, metal oxide precursor contact, and oxidation processes. The lattice-shaped protrusions with metal oxide as the main component achieve high yield and high aspect ratio micro-patterning.

Benefits of technology

An inorganic wavelength plate with excellent heat resistance and durability has been developed, which is suitable for high-intensity light source instruments and can stably provide the required phase difference to meet the requirements of high-performance equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121703975A_ABST
    Figure CN121703975A_ABST
Patent Text Reader

Abstract

Provided is a structurally birefringent inorganic wavelength plate having excellent heat resistance and durability and having a fine pattern. Furthermore, the present invention provides a method for producing an inorganic wavelength plate, which has a high yield even in the form of a fine pattern, can easily achieve a desired phase difference, and can stably obtain the desired phase difference. An inorganic wavelength plate having a wire grid structure is obtained by selective interaction between a polymer having a repeating unit containing a carbonyl group and a metal oxide precursor, the inorganic wavelength plate being provided with a transparent substrate and lattice-shaped protrusions, and lattice-shaped protrusions that are arranged on at least one surface of the transparent substrate at a pitch shorter than the wavelength of light in the use frequency band and extend in a predetermined direction, the lattice-shaped protrusions being mainly composed of a metal oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application with the application date of May 7, 2019, the application number of 201980028707.4 (international application number of PCT / JP2019 / 018267), and the invention name of "Inorganic wave plate and manufacturing method thereof". TECHNICAL FIELD

[0002] The present application relates to an inorganic wave plate and a manufacturing method thereof. BACKGROUND

[0003] A wave plate is an element that imparts a specific phase difference to light, and is mounted on various optical instruments. In general, there are known a 1 / 2 wave plate, a 1 / 4 wave plate, or a phase difference plate that imparts a phase difference smaller than these, and in the case of incident linearly polarized light, if the angle of the optical axis of the wave plate with respect to the linearly polarized light is set to θ , the 1 / 2 wave plate has a function of emitting linearly polarized light rotated by 2 θ angles. In addition, for example, if linearly polarized light inclined by 45° with respect to the optical axis of the wave plate is incident in-plane, the 1 / 4 wave plate has a function of converting it into circularly polarized light.

[0004] In the past, as a wave plate, there has been known a so-called phase difference film obtained by imparting orientation to a high molecular film (see Patent Literature 1). However, since the wave plate based on the high molecular film is easily deteriorated by heat or UV light, there is a problem in durability. For example, for an instrument using a light source such as laser light having a high light intensity, there are cases where the heat and light resistance is not sufficient.

[0005] As another type of wave plate, there has been known a structural birefringence type wave plate that utilizes birefringence based on a lattice structure composed of lines and a concave-convex pattern of spaces (see Patent Literature 2). The structural birefringence type wave plate that forms a lattice structure is excellent in that a uniform performance can be embodied, compared to a wave plate of a high molecular film that imparts a desired orientation by stretching a film material.

[0006] Here, in recent years, in various electronic devices, the requirements for high density, high integration, and high performance are increasingly high, and a more fine pattern is also required for the structural birefringence type wave plate. However, the wave plate that utilizes structural birefringence requires not only a structure of a wavelength order, but also a high aspect ratio to obtain a phase difference (1 / 4, 1 / 2) that is generally required. For this reason, it is extremely difficult to manufacture a structural birefringence type wave plate that satisfies the required level. λ λ

[0007] PRIOR ART DOCUMENTS PATENT LITERATURE ​​Patent Literature 1: Japanese Patent Application Laid-Open (JP A) No. 11-231132 Patent Literature 2: Japanese Patent Application Laid-Open (JP A) No. 2013-200908 SUMMARY

[0008] PROBLEMS TO BE SOLVED BY THE INVENTION The present application was made in view of the above-described background art, and aims to provide a structural birefringence type inorganic wavelength plate having a fine pattern, which is excellent in heat resistance and durability. Further, the present application aims to provide a manufacturing method of an inorganic wavelength plate, which is high in yield even for a fine pattern, and which is easy to achieve a desired phase difference while stably obtaining the desired phase difference.

[0009] MEANS FOR SOLVING THE PROBLEMS The present inventors found that if a selective interaction of a polymer having a repeating unit containing a carbonyl group with a metal oxide precursor is utilized, a structural birefringence type inorganic wavelength plate, which is high in yield even for a fine pattern, excellent in heat resistance and durability, and which is easy to achieve a desired phase difference while stably obtaining the desired phase difference, can be obtained, and thus completed the present application.

[0010] That is, the present application relates to an inorganic wavelength plate, which is an inorganic wavelength plate having a wire grid structure, and which comprises a transparent substrate and a lattice-shaped protrusion arranged on the transparent substrate at a pitch shorter than the wavelength of light used in a band, and extending in a prescribed direction, the lattice-shaped protrusion mainly comprising a metal oxide.

[0011] The lattice-shaped protrusion can have two or more different pitches mixed therein.

[0012] The metal oxide can be AI2O3.

[0013] The metal oxide can be TiO2.

[0014] Further, another aspect of the present application relates to a manufacturing method of an inorganic wavelength plate, which is a manufacturing method of an inorganic wavelength plate having a wire grid structure, and which comprises the following steps: a polymer lattice formation step of arranging a polymer having a repeating unit containing a carbonyl group into a lattice extending in a prescribed direction on at least one surface of a transparent substrate, to form a polymer lattice; a metal oxide precursor contact step of bringing a vapor of a metal oxide precursor into contact with the polymer lattice, to bind a metal of the metal oxide precursor to the carbonyl group, and form a metal oxide precursor binding portion; and an oxidation step of bringing water vapor into contact with the lattice having the metal oxide precursor binding portion, to oxidize the metal oxide precursor binding portion, and form a metal oxide lattice mainly comprising a metal oxide.

[0015] The above-mentioned metal oxide precursor contacting step and the above-mentioned oxidation step are repeated as a cycle, and the above-mentioned cycle can be repeated multiple times.

[0016] The arrangement of the polymer having a repeating unit containing a carbonyl group in the above-mentioned polymer lattice forming step can be formed by self-assembly of the above-mentioned polymer having a repeating unit containing a carbonyl group.

[0017] The above-mentioned polymer lattice forming step can use a physical guide.

[0018] The above-mentioned repeating unit containing a carbonyl group can be a unit from methyl methacrylate.

[0019] The above-mentioned polymer having a repeating unit containing a carbonyl group can be a block copolymer containing a molecular chain composed of polymethyl methacrylate and a molecular chain composed of polystyrene.

[0020] An etching step can be further included in which etching is performed using the above-mentioned metal oxide lattice as a mask.

[0021] Effects of the Invention Since the inorganic wavelength plate according to the present invention is composed only of inorganic materials, the heat resistance and durability are excellent compared to wavelength plates based on polymer materials. Therefore, the inorganic wavelength plate according to the present invention can also be sufficiently applied to instruments using light sources with high light intensity such as laser light.

[0022] In addition, as the metal oxide constituting the lattice-shaped protrusions, if a high-refractive material (e.g., TiO2) is selected, an inorganic wavelength plate of a thin film can be realized, and a zero-order wavelength plate can be obtained.

[0023] In addition, if the arrangement of the polymer having a repeating unit containing a carbonyl group is formed into a fine arrangement, an inorganic wavelength plate of lattice-shaped protrusions with a finer pattern can be realized, and as a result, the requirement for high-performance devices can be satisfied.

[0024] In addition, according to the manufacturing method of the inorganic wavelength plate according to the present invention, an inorganic wavelength plate of a structural birefringent type can be manufactured at a high yield even for a fine pattern.

[0025] Furthermore, if etching is performed using the lattice-shaped protrusions with a metal oxide as a main component as a mask, lattice-shaped protrusions with a higher aspect ratio can be produced, and therefore an inorganic wavelength plate in which the desired phase difference is easily realized and the desired phase difference is stably obtained can be obtained. BRIEF DESCRIPTION OF DRAWINGS

[0026] [ Figure 1 ] is a drawing showing one embodiment of the present invention.

[0027] [ Figure 2FIG. 1 is a photograph showing an embodiment of the present application.

[0028] [ Figure 3 FIG. 2 is a photograph of an embodiment having a guide device pattern. DETAILED DESCRIPTION

[0029] Hereinafter, embodiments of the present application will be described in detail with reference to the accompanying drawings.

[0030] [Inorganic wavelength plate] The inorganic wavelength plate of the present application is a wavelength plate of the structural birefringence type that utilizes birefringence based on a lattice structure. Specifically, it relates to an inorganic wavelength plate that is an inorganic wavelength plate having a wire grid structure, and has a transparent substrate and a lattice-shaped protrusion that is arranged on at least one surface of the transparent substrate at a pitch shorter than the wavelength of light in the use frequency band and extends in a prescribed direction, the main component of the lattice-shaped protrusion being a metal oxide. Note that the inorganic wavelength plate of the present application can have other layers in addition to the transparent substrate and the lattice-shaped protrusion.

[0031] Figure 1 (f) and Figure 2 (d) are cross-sectional schematic diagrams showing the inorganic wavelength plate according to an embodiment of the present application. As shown in Figure 1 (f) and Figure 2 (d), the inorganic wavelength plate has a transparent substrate 1 and a lattice-shaped protrusion that is arranged on one surface of the transparent substrate 1 at a pitch shorter than the wavelength of light in the use frequency band and is composed of a region 4 having a metal oxide as the main component. That is, the inorganic wavelength plate of the present application has a wire grid structure in which the lattice-shaped protrusion having a metal oxide as the main component is arranged in a one-dimensional lattice on at least one surface of the transparent substrate.

[0032] Here, a structurally birefringent wavelength plate refers to a wavelength plate that utilizes birefringence based on a lattice structure composed of concave and convex patterns in lines and space. For example, as described in "Submicrometer periodicity gratings asartificial anisotropic dielectrics" (Dale C. Flanders, Appl. Phys. Lett. 42(6), 15 March 1983), wavelength plates with different refractive indices in directions parallel and perpendicular to the structure can be realized by utilizing the material or concave-convex ratio of its microstructure. Since the speed of light in a material is inversely proportional to the refractive index, the speed of light changes relative to polarized waves in each direction. As a result, the phase of the incident light changes before and after the structurally birefringent wavelength plate. The birefringence of materials such as crystal or calcite is an inherent property of the material and hardly changes. In contrast, the optical performance of a structurally birefringent wavelength plate can be controlled by changing the size of the concave-convex periodic structure or the constituent material.

[0033] (Transparent substrate) As a transparent substrate ( Figure 1 The transparent substrate 1 in the text can be any substrate that displays light transmittance for the operating frequency band; there are no particular limitations, and it can be selected appropriately according to the purpose. "Displaying light transmittance for the operating frequency band" does not mean that the transmittance of the operating frequency band light is 100%, but only that the light transmittance can maintain its function as a wavelength plate. Examples of operating frequency band light include visible light with wavelengths of approximately 380nm to 810nm.

[0034] There are no particular limitations on the shape of the main surface of the transparent substrate; a shape appropriate to the purpose (e.g., a rectangular shape) can be selected. The average thickness of the transparent substrate is preferably, for example, 0.1 mm to 1 mm.

[0035] As the constituent material of the transparent substrate, a material with a refractive index of 1.1 to 2.2 is preferred, and materials without optically active properties are suitable. From the perspective of cost and light transmittance, glass, especially quartz glass (refractive index 1.46) or soda lime glass (refractive index 1.51), is preferred. There are no particular limitations on the composition of the glass material; for example, inexpensive glass materials such as silicate glass, which are widely used as optical glass, can be used.

[0036] (lattice-shaped protrusions) Grid-like protrusions (e.g., Figure 1The region 4) in (f) in which a metal oxide is the main component is formed on one side of the transparent substrate at a pitch shorter than the wavelength of light used in the band, and is arranged in a band shape in a prescribed direction. That is, the inorganic wavelength plate of the present application has a concave-convex periodic structure in which the lattice-shaped convex portions and the concave portions that become the grooves are periodically repeated. Note that in the present application, other layers can be present between the transparent substrate and the lattice-shaped convex portions.

[0037] The lattice-shaped convex portions in the inorganic wavelength plate of the present application can have other components in addition to the metal oxide as the main component. In addition, layers other than the layer in which the metal oxide is the main component can be present in the lattice-shaped convex portions. For example, the inorganic wavelength plate of the present application also includes the following aspect: a layer in which the metal oxide is the main component is used as a mask to perform etching, and a cavity (digging) is formed in the concave portions. In this case, the lattice-shaped convex portions are composed of a layer in which the metal oxide layer is the main component and a layer formed by the cavity.

[0038] In the inorganic wavelength plate of the present application, the pitch of the lattice-shaped convex portions is not particularly limited as long as it is shorter than 1 / 2 of the wavelength of light used in the band, but it is desirable to be smaller. In the case of visible light applications, since the wavelength in the blue region is 400 nm, it is desirable for the pitch to be less than 200 nm. The periodic length of the lattice-shaped convex portions in the inorganic wavelength plate of the present application can be controlled by the molecular weight of the polymer having a repeating unit containing a carbonyl group used as the material. As a result, a small pitch of 100 nm or less can be easily produced.

[0039] The pitch of the lattice-shaped convex portions can be measured by observation using a scanning electron microscope or a transmission electron microscope. For example, the pitch can be measured at four arbitrary points using a scanning electron microscope or a transmission electron microscope, and the arithmetic mean value thereof can be used as the pitch of the lattice-shaped convex portions. Hereinafter, this measurement method is referred to as the electron microscope method.

[0040] In addition, the lattice-shaped convex portions in the inorganic wavelength plate of the present application can have two or more different pitches mixed therein. In the present application, in order to achieve the desired optical performance, the lattice-shaped convex portions and the concave portions that become the grooves preferably form a periodic structure in which the arrangement is periodically repeated. For this reason, even in the case where two or more different pitches are mixed, it is preferable to form a periodic arrangement.

[0041] The material constituting the lattice-shaped protrusions is not particularly limited, and can be a material in which a metal oxide formed from a precursor that selectively interacts with a polymer having a repeating unit containing a carbonyl group is used as a main component. Examples include AI2O3, TiO2, and the like. Of these, AI2O3 is preferable from the viewpoint of moisture resistance. In the case of using AI2O3, a wavelength plate having excellent water vapor barrier properties can be achieved. In addition, TiO2 having a high refractive index (refractive index of about 2.0) is preferable from the viewpoint of allowing the inorganic wavelength plate to be thinned. In the present application, by selecting a material having a high refractive index, a zero-order wavelength plate can be achieved.

[0042] Since the inorganic wavelength plate of the present application is a structural birefringence type wavelength plate, by changing the size or the material constituting the concave-convex periodic structure of the lattice-shaped protrusions, the optical properties to be embodied can be controlled. For example, in the case where the lattice-shaped protrusions are constituted by a material in which AI2O3 is used as a main component, since the refractive index of AI2O3 is about 1.6, if a 1 / 4 wavelength plate having a wavelength of 450 nm is produced in such a manner that the ratio of the convex portion to the concave portion (L / S) = 1, the required film thickness is about 250 nm. As described above, if TiO2 having a high refractive index (refractive index of about 2.0) is used to produce a 1 / 4 wavelength plate having a wavelength of 450 nm in such a manner that the ratio of the convex portion to the concave portion (L / S) = 1, the required film thickness is about 110 nm or so, and the resulting wavelength plate can be thinned.

[0043] The film thickness of the lattice-shaped protrusions is not particularly limited, and can be in the range of 30 nm to 3000 nm, for example. Note that the film thickness of the lattice-shaped protrusions can be measured by the electron microscope method described above, for example.

[0044] In the case where the inorganic wavelength plate of the present application is a scheme in which lattice-shaped protrusions in which a metal oxide is used as a main component are used as a mask to perform etching, and a cavity is formed in the concave portions, the lattice-shaped protrusions are constituted by a layer in which a metal oxide is used as a main component and a layer in which the cavity is formed. Also, in the inorganic wavelength plate of the present application, since other layers can be present between the transparent substrate and the lattice-shaped protrusions, the lattice-shaped protrusions are sometimes constituted by a layer in which a metal oxide is used as a main component, other layers, and / or the transparent substrate. Note that, as the other layers, a layer constituted by silica (SiO2) or tantalum oxide (Ta2O5) as a high refractive index material, and the like can be exemplified.

[0045] (Protective film) In addition, the inorganic wavelength plate of the present application can cover at least the surface of the light incident side with a protective film within a range that does not affect the optical properties. The protective film is preferably composed of a dielectric, and for example, SiO2may be preferably used. By having the protective film, it is possible to expect an improvement in mechanical properties, and an effect of protecting the concave-convex shape.

[0046] (waterproof film) In addition, the inorganic wavelength plate of the present application can cover at least the surface of the light incident side with a waterproof film. The waterproof film is preferably organic, and for example, a fluorine-based silane compound such as perfluorodecyltriethoxysilane (FDTS) can be preferably used. Thereby, it is possible to prevent impurities from intruding into the inorganic wavelength plate, and at the same time, it is possible to improve reliability such as moisture resistance.

[0047] [Method for manufacturing inorganic wavelength plate] The method for manufacturing the inorganic wavelength plate of the present application has at least a polymer lattice forming step, a metal oxide precursor contacting step, and an oxidation step.

[0048] (polymer lattice forming step) In the polymer lattice forming step, a polymer having a repeating unit including a carbonyl group is aligned on at least one surface of a transparent substrate into a lattice extending in a prescribed direction, and a polymer lattice is formed.

[0049] {polymer having a repeating unit including a carbonyl group} In the present application, in the metal oxide precursor contacting step that follows, a metal oxide precursor binds to a carbonyl group contained in the polymer having a repeating unit including a carbonyl group. For this reason, in the present application, the carbonyl group is an essential constituent element, but the polymer having a repeating unit including a carbonyl group used is not particularly limited as long as it has a carbonyl group in the repeating unit of the polymer.

[0050] It should be noted that the polymer used in the manufacturing method of the inorganic wavelength plate of the present invention, which has repeating units containing carbonyl groups, preferably has self-assembly properties. If the polymer has self-assembly properties, it can easily form an arrangement of lattice extending in a predetermined direction through self-assembly. Examples of such polymers having self-assembly properties and having repeating units containing carbonyl groups include: block copolymers containing molecular chains of polymethyl methacrylate and polystyrene; block copolymers containing molecular chains of polyethyl methacrylate and polystyrene; block copolymers containing molecular chains of polytert-butyl methacrylate and polystyrene; block copolymers containing molecular chains of polymethyl methacrylate and polystyrene; block copolymers containing molecular chains of polyethyl methacrylate and polystyrene; block copolymers containing molecular chains of polytert-butyl methacrylate and polystyrene; etc. Among these, block copolymers having units derived from methyl methacrylate are preferred from the perspective of excellent self-assembly performance.

[0051] In particular, the polymer containing repeating units comprising carbonyl groups used in the manufacturing method of the inorganic wavelength plate of the present invention is preferably a block copolymer comprising molecular chains of polymethyl methacrylate and molecular chains of polystyrene. The molecular chains of polymethyl methacrylate possess excellent self-assembly properties, allowing blocks comprising polymethyl methacrylate molecular chains and blocks comprising polystyrene molecular chains to self-assemble and separate into lamellae, forming a structure with regular domains and periodic patterns. The shape or size of the domains can be adjusted by designing the block copolymer, and nanoscale periodic lamellae structures can also be formed.

[0052] {Alignment based on photolithography} In the polymer lattice formation process, there is no particular limitation on the method of arranging polymers having repeating units containing carbonyl groups on at least one side of a transparent substrate into a lattice extending in a predetermined direction, and it can be carried out, for example, by photolithography.

[0053] Figure 1 The paper demonstrates a method for arranging polymers containing repeating carbonyl groups into a lattice extending in a specified direction using photolithography.

[0054] To arrange the elements into a grid extending along a specified direction using photolithography, firstly, as... Figure 1 As shown in (b), a layer composed of a polymer having repeating units containing carbonyl groups is formed on at least one side of the transparent substrate 1. Figure 1(b) is a region 2) having a molecular chain composed of polymethyl methacrylate (PMMA).

[0055] Next, on the layer (in (b), a region 2) having a molecular chain composed of polymethyl methacrylate (PMMA) formed above the layer (in (a), a region 1) having a molecular chain composed of a polymer having a repeating unit containing a carbonyl group, a photoresist is disposed, and after exposure and transfer of a photomask by photolithography, development processing is performed, forming a line-and-space (L / S) pattern based on the resist 5 as shown in (c). Figure 1 (b) is a region 2) having a molecular chain composed of polymethyl methacrylate (PMMA). Figure 1 (c).

[0056] Next, etching is performed using the L / S pattern (the pattern based on the resist 5 in (c) ) obtained as a mask, and the layer (in (b), a region 2) having a molecular chain composed of polymethyl methacrylate (PMMA) is removed. Figure 1 (c). Figure 1 (b) is a region 2) having a molecular chain composed of polymethyl methacrylate (PMMA). Figure 1 (d) ).

[0057] Finally, as shown in (e), the resist 5 is dissolved and removed using a chemical reagent or the like, and thus a polymer lattice in which a polymer having a repeating unit containing a carbonyl group is arranged in a lattice extending in a prescribed direction is obtained. Figure 1 (e).

[0058] {Arrangement based on self-assembly} In the polymer lattice formation process, as another method for arranging a polymer having a repeating unit containing a carbonyl group in a lattice extending in a prescribed direction on at least one face of a transparent substrate, for example, a method in which a polymer having a self-assembly property is caused to self-assemble can be cited.

[0059] As described above, as a polymer having a self-assembly property and having a repeating unit containing a carbonyl group, for example, a polymer having a unit from methyl methacrylate as a repeating unit can be cited. Among these, a block copolymer containing a molecular chain composed of polymethyl methacrylate and a molecular chain composed of polystyrene is preferable. The block copolymer containing a molecular chain composed of polymethyl methacrylate and a molecular chain composed of polystyrene phase separates into a lamellar structure having a regular domain structure, forming a periodic pattern. By designing this block copolymer, the shape or size of the domain can be adjusted, and a pattern formed from a lamellar structure of a periodicity of the order of nanometers can also be realized.

[0060] Note that in the case of using a block copolymer having a self-assembly property, a structure having a regular domain such as a phase-separated lamella to form a periodic pattern, a metal oxide precursor contact process and an oxidation process described later are then performed to convert a polymer having a repeating unit including a carbonyl group into a metal oxide. Also, a process of removing a region composed of a molecular chain not having a carbonyl group using a chemical reagent or the like is finally performed.

[0061] Self-assembly using a physical guide device Also, a polymer having a self-assembly property and having a repeating unit including a carbonyl group is housed between walls called a physical guide device to make it easier to form a pattern. In the case of using a physical guide device, the width of the physical guide device and the width of a pattern formed by phase separation by self-assembly do not necessarily have to be the same. By making them different, an inorganic wavelength plate having a lattice-shaped convex portion with two or more different pitches can be finally realized.

[0062] Figure 2 A method of using a physical guide device to arrange a polymer having a repeating unit including a carbonyl group into a lattice extending in a prescribed direction is shown in Figure 2 In the scheme shown in

[0063] In the method using a physical guide device, first, a guide device pattern having a prescribed pitch interval is formed by photolithography or the like (a guide device 6 in Figure 2 Next, a polymer having a self-assembly property and having a repeating unit including a carbonyl group is housed in the recesses of the formed physical guide device pattern, phase separates into a structure having a regular domain by self-assembly, and a pattern is formed. The polymer that performs self-assembly more easily forms a periodic lamella structure along the physical guide device due to the presence of the physical guide device, and as a result, a polymer lattice in which a polymer having a repeating unit including a carbonyl group is arranged into a lattice extending in a prescribed direction can be produced.

[0064] In the scheme shown in Figure 2 In the scheme shown in Figure 2(a) is a polymer lattice with regions 2) consisting of molecular chains made of polymethyl methacrylate (PMMA) arranged in a lattice extending in a specified direction.

[0065] It should be noted that, as described above, when using block copolymers with self-assembly properties, performing the metal oxide precursor contacting process and oxidation process described later will transform the regions of molecular chains containing repeating units including carbonyl groups (in...) Figure 2 (a) represents the region 2) containing molecular chains composed of polymethyl methacrylate (PMMA). After conversion to metal oxides, the following final step is performed: the region consisting of molecular chains without carbonyl groups is removed using chemical reagents, etc. Figure 2 (b) is region 3, which has molecular chains composed of polystyrene, and a physical guiding device (in...). Figure 2 (b) is the guide device 6).

[0066] There are no particular limitations on the method for making the physical guidance device. For example, the following methods can be listed: the material to be the guidance device is dissolved in a solvent, then coated and dried to form a coating film, a photoresist is coated on the formed coating film to form a photoresist layer, the photoresist layer is exposed / developed to form a photoresist pattern, the obtained photoresist pattern is used to etch the coating film to become the guidance device, and then the photoresist is stripped off to obtain the final physical guidance device.

[0067] There are no particular limitations on the material of the physical guide device; for example, polymers can be used. Among them, polymers with the property that their shape does not easily collapse even after the above-described manufacturing process of the physical guide device are preferred.

[0068] The solvent used to dissolve the material that becomes the guiding device should be appropriately selected based on factors such as compatibility with the polymer that becomes the guiding device and its drying properties. Preferred combinations of materials and solvents for the guiding device include, for example, random copolymers of polymethyl methacrylate (PMMA) / polystyrene (PS) and combinations with toluene or propylene glycol monoethyl ether acetate.

[0069] (Metal oxide precursor contact process) In the metal oxide precursor contact process, the vapor of the metal oxide precursor is brought into contact with the polymer lattice formed by the polymer lattice formation process, so that the metal of the metal oxide precursor combines with the carbonyl group in the polymer to form the metal oxide precursor bonding part.

[0070] The metal oxide precursor contact process in this invention is in Figure 1 In is from Figure 1 (e) To Figure 1 (f) is implemented during the transition process, while Figure 2 In is from Figure 2(a) is carried out during the transition to Figure 2 (b) is carried out during the transition to Figure 1 (e) is carried out in order to form region 2 of the molecular chain composed of the repeating unit containing a carbonyl group in (a) Figure 1 (f) is carried out in order to form region 4 in which a metal oxide is the main component in (c), and this is also carried out in order to form region 2 of the molecular chain composed of the repeating unit containing a carbonyl group in (a) Figure 2 (a) is carried out during the transition to Figure 2 (b) is carried out during the transition to

[0071] {Metal oxide precursor} In the metal oxide precursor contacting step, a substance that becomes a metal oxide precursor is brought into contact with a carbonyl group in the polymer that forms the polymer lattice in the form of a vapor. The metal oxide precursor supplied as a vapor has the property of selectively binding to a carbonyl group. The metal oxide precursor binds to a molecular chain having a repeating unit containing a carbonyl group and grows on the molecular chain, but does not substantially react with a molecular chain that does not have a carbonyl group.

[0072] Therefore, the metal oxide precursor that selectively binds to a carbonyl group, which can be used in the present application, is a compound that exhibits the property of a Lewis acid, and examples thereof include trimethylaluminum (TMA), titanium tetrachloride (TiCl4), and the like. In the case of using trimethylaluminum (TMA), aluminum oxide (Al2O3) is finally obtained in the form of a metal oxide, and in the case of using titanium tetrachloride (TiCl4), titanium oxide (TiO2) is finally obtained in the form of a metal oxide.

[0073] The contact of the supplied metal oxide precursor with the substrate can be performed, for example, as follows. The substrate is arranged in a chamber that can maintain a vacuum. Next, the chamber is vacuumed using a dry pump or the like. In order to promote the reaction, the substrate temperature is set to a range of 150 to 250°C. Next, the metal oxide precursor is introduced into the chamber. The vapor pressure at this time is preferably set to a range of 0.1 to 1 mTorr. Further, the contact time is preferably set to a range of 300 to 600 seconds. If this range is used, the reaction proceeds sufficiently. After the prescribed contact time has elapsed, the chamber is again evacuated.

[0074] (Oxidation step) In the oxidation step, water vapor is brought into contact with the lattice having a metal oxide precursor binding portion formed by the metal oxide precursor contacting step, and the metal oxide precursor binding portion is oxidized to form a metal oxide lattice in which a metal oxide is the main component. Since the resulting metal oxide lattice has a metal oxide as the main component, it becomes a lattice-shaped protrusion that has high etching resistance and also has improved heat resistance.

[0075] The oxidation step in the present application is performed in a transition process from Figure 1 (e) to Figure 1 (f) and in a transition process from Figure 1 (a) to Figure 2 (b). That is, this is a step to form region 2 of the molecular chain composed of the repeating unit containing a carbonyl group in Figure 2 (e) into region 4 containing a metal oxide as a main component in Figure 2 (f), and also this is a step to form region 2 of the molecular chain composed of the repeating unit containing a carbonyl group in Figure 1 (a) into region 4 containing a metal oxide as a main component in Figure 2 (b). Figure 2 Figure 2 The oxidation step is performed after the metal oxide precursor contact step. This is because the object to be oxidized in the oxidation step is the lattice having the metal oxide precursor bonding portion formed by the metal oxide precursor contact step. In the lattice having the metal oxide precursor bonding portion, the metal oxide of the metal oxide precursor bonding portion is oxidized using water vapor to be converted into a metal oxide.

[0076] The pressure of the water vapor supplied in the oxidation step is preferably 1 atm or a pressure close thereto, and the substrate temperature is preferably set to a range of 150 to 250°C. Further, the contact time is preferably set to a range of 300 to 600 seconds. If this range, oxidation is particularly and sufficiently performed without any problem.

[0077] (repeat) Note that in the method for manufacturing the inorganic wavelength plate of the present application, the above-described metal oxide precursor contact step and the above-described oxidation step are preferably repeated as one cycle, and these steps are repeatedly performed for a plurality of cycles.

[0078] That is, in , the above-described metal oxide precursor contact step and the oxidation step are preferably repeatedly performed in a transition process from

[0079] (e) to Figure 2 (f), and in Figure 2 , the above-described metal oxide precursor contact step and the oxidation step are preferably repeatedly performed in a transition process from Figure 2 (a) to Figure 2 (b), and finally Figure 2 (f) or λ (b) is formed. λ Figure 2

[0080] ​​By repeating the cycle of the metal oxide precursor contacting step and the oxidation step several times, the proportion of conversion from the molecular chain composed of repeating units containing a carbonyl group to the metal oxide can be further increased, and ultimately almost complete metal oxide can be achieved. The number of repetitions in the present application is preferably 7 or more, and most preferably 10 or more.

[0081] (lattice-shaped protrusion forming step) In the manufacturing method of the inorganic wavelength plate of the present application, in the case where a block copolymer composed of a molecular chain having repeating units containing a carbonyl group and a molecular chain not having a carbonyl group is used as the polymer having repeating units containing a carbonyl group, the lattice-shaped protrusion forming step is implemented.

[0082] In the case where a block copolymer composed of a molecular chain having repeating units containing a carbonyl group and a molecular chain not having a carbonyl group is used, the lattice-shaped protrusion forming step becomes a necessary step, which is a step implemented after the metal oxide precursor contacting step and the oxidation step are implemented several times to convert the polymer having repeating units containing a carbonyl group to a metal oxide, if necessary. Specifically, after the polymer having repeating units containing a carbonyl group is converted to a metal oxide, the region composed of a molecular chain not having a carbonyl group and the physical guide means used, if any, are removed using a chemical reagent or the like, thereby forming a lattice-shaped protrusion composed mainly of a metal oxide.

[0083] For example, in the scheme of using a physical guide means as a scheme Figure 3 is implemented between Figure 2 (b) and Figure 3 (c), the region 3 having a molecular chain composed of polystyrene and the guide means 6 composed of a molecular chain not having a carbonyl group are removed using a chemical reagent or the like, and a lattice-shaped protrusion composed of the region 4 composed mainly of a metal oxide is formed.

[0084] (etching step) The manufacturing method of the inorganic wavelength plate of the present application can further have an etching step of etching with the metal oxide lattice formed by the oxidation step as a mask. The etching step is a step implemented between Figure 2 in Figure 2 (c) and Figure 3 (d). Figure 2 In (d), the following scheme is shown: a cavity is formed on the transparent substrate 1 by etching, and a part of the transparent substrate 1 constitutes a part of the lattice-shaped protrusion.

[0085] However, in the present application, another layer can exist between the layer having metal oxide as a main component constituting the lattice-shaped convex portion and the transparent substrate. For this reason, in the etching step, a cavity is sometimes formed only in the other layer, or in both the other layer and the transparent substrate. In the case where the cavity is formed only in the other layer, the lattice-shaped convex portion is constituted by the layer having metal oxide as a main component and the other layer. In the case where the cavity is formed in both the other layer and the transparent substrate, the lattice-shaped convex portion is constituted by the layer having metal oxide as a main component and the other layer, and a part of the transparent substrate.

[0086] Since the inorganic wavelength plate of the present application is a wavelength plate of a structural birefringence type, by changing the size of the periodic structure of the lattice-shaped convex portion, the optical performance to be embodied can be controlled. Further, in order to obtain a phase difference (λ / 4, λ / 2) generally required, a high aspect ratio is needed. In the present application, etching is performed using a metal oxide lattice as a mask, and a cavity is formed in the recess, whereby a lattice-shaped convex portion having a high aspect ratio can be realized. In addition, the size can be adjusted to a desired size by etching, whereby a desired optical characteristic can be embodied. Figure 2 / 4、 ​ / 2), a high aspect ratio is needed. In the present application, etching is performed using a metal oxide lattice as a mask, and a cavity is formed in the recess, whereby a lattice-shaped convex portion having a high aspect ratio can be realized. In addition, the size can be adjusted to a desired size by etching, whereby a desired optical characteristic can be embodied.

[0087] The etching method is not particularly limited, and for example, a dry etching method using an etching gas corresponding to the etching object can be exemplified. For example, in the case where quartz is used as the transparent substrate, by using CF4as the etching gas, etching can be performed.

[0088] (Protective film imparting step) The manufacturing method of the inorganic wavelength plate of the present application can have a protective film imparting step of covering at least the surface of the light incident side with a protective film. In the protective film imparting step, for example, a protective film is formed on at least the surface of the wavelength plate (the surface on which the wire grid is formed) by Chemical Vapor Deposition (CVD) or Atomic Layer Deposition (ALD). As the protective film, a film composed of a dielectric is preferred, and for example, SiO2may be preferably used.

[0089] (Water-repellent film imparting step) The manufacturing method of the inorganic wavelength plate of the present application can have a water-repellent film imparting step of covering at least the surface of the light incident side with a water-repellent film. In the water-repellent film imparting step, for example, a water-repellent film can be formed on at least the surface of the wavelength plate (the surface on which the wire grid is formed) by the above-described CVD or ALD. As the water-repellent film, a film composed of an organic material is preferred, and for example, a fluorine-based silane compound such as perfluorodecyltriethoxysilane (FDTS) can be preferably used.

[0090] [Use] The inorganic wavelength plate of the present application can be mounted on various optical instruments. As the optical instruments, there can be listed liquid crystal projectors, head-up displays, digital cameras, and the like. In addition, since the inorganic wavelength plate is excellent in heat resistance and durability as compared with the organic wavelength plate composed of an organic material, it can be particularly suitable for uses such as liquid crystal projectors, head-up displays, and the like, which require heat resistance and durability. Example

[0091] Next, the embodiment of the present application will be described with reference to ​ and ​ The present application is not limited to the embodiment.

[0092] Example 1 In Example 1, the following method was carried out using a physical directing device: a polymer having self-assembly properties and having a repeating unit containing a carbonyl group was housed between the walls of the directing device to form a pattern.

[0093] [Manufacture of directing device pattern] A random copolymer of a molecular chain composed of polymethyl methacrylate and a molecular chain composed of polystyrene (molecular weight: about 40,000) was dissolved in toluene to a concentration of 1.5 mass%. Next, the resulting solution was spin-coated to manufacture a neutral layer. Further, a photoresist layer was formed by applying a photoresist on the manufactured neutral layer. Next, by exposing / developing the photoresist layer, a resist pattern was manufactured. Using the resulting resist pattern, the neutral layer was etched by O2 plasma, and then the resist was peeled off, thereby forming a directing device pattern of the neutral layer (directing device 6 in (a)). The film thickness (height) of the directing device was 13 nm. ​ (a) shows a photograph of the resulting directing device pattern. ​

[0094] [Embedding of block copolymer] A block copolymer containing a molecular chain composed of polymethyl methacrylate and a molecular chain composed of polystyrene was housed between the walls of the directing device (directing device 6 in (a)) of the resulting directing device pattern. The molecular weight of the block copolymer used was 113,000, and the composition ratio of the molecular chain composed of polymethyl methacrylate to the molecular chain composed of polystyrene was about 1:1. Note that, at the time of housing, toluene was used as a solvent, and the concentration of the copolymer was 1.5 mass%, and spin coating was carried out. ​

[0095] [Self-assembly of block copolymer] ​​The block copolymer containing molecular chains composed of polymethyl methacrylate and molecular chains composed of polystyrene was self-assembled between the guide devices 6 by heat treatment in a vacuum at 240°C for 12 hours, phase-separated into a structure having regular domains. As a result, as shown in ​ (a), a periodic lamellar structure in which regions 2 having molecular chains composed of polymethyl methacrylate (PMMA) and regions 3 having molecular chains composed of polystyrene alternately exist along the guide devices 6 was formed. A photograph of the formed periodic lamellar structure is shown in ​ (b). The periodic length of the produced periodic lamellar structure was about 45 nm.

[0096] [metal oxide precursor contact step] Next, the vapor of trimethylaluminum (TMA) was contacted with the obtained periodic lamellar structure, and the metal of the metal oxide precursor was bonded to the carbonyl group in the region 2 having molecular chains composed of polymethyl methacrylate (PMMA), and a metal oxide precursor bonding portion was formed. The environment in which the vapor was supplied was a vacuum chamber, the substrate temperature was set to 200°C, the pressure was set to 1 mTorr, the supply time was set to 0.3 seconds, and the holding time was set to 600 seconds.

[0097] [oxidation step] Next, the metal oxide precursor bonding portion was oxidized by contacting water vapor with the periodic lamellar structure in which the metal oxide precursor bonding portion was formed, and as shown in ​ (b), a metal oxide lattice composed of a region 4 in which a metal oxide was the main component was formed. Note that the metal oxide formed in this embodiment was AI2O3. The environment in which the water vapor was supplied was a vacuum chamber, the substrate temperature was set to 200°C, the pressure was set to 1 mTorr, the supply time was set to 0.3 seconds, and the holding time was set to 600 seconds.

[0098] [lattice-shaped protrusion formation step] Next, the region 3 having molecular chains composed of polystyrene and the guide devices 6 were removed, and a lattice-shaped protrusion composed of AI2O3 was formed ​ (c), and an inorganic wavelength plate was obtained. At the time of removing the region 3 having molecular chains composed of polystyrene and the guide devices 6, ashing was performed using O2 plasma. The pitch of the lattice-shaped protrusion of the obtained inorganic wavelength plate was 45 nm, and the height was 13 nm.

[0099] Symbol explanation 1: transparent substrate; 2: region having molecular chains composed of polymethyl methacrylate (PMMA); 3: region having molecular chains composed of polystyrene; 4: region in which a metal oxide is the main component 5: resist 6: guide

Claims

1. A method for manufacturing an inorganic wavelength plate, specifically a method for manufacturing an inorganic wavelength plate with a wire grid structure. The aforementioned inorganic wavelength plate comprises a transparent substrate and lattice-shaped protrusions arranged on at least one side of the transparent substrate at a spacing shorter than the wavelength of light in use, and extending in a predetermined direction. The aforementioned spacing is above 45nm and below 100nm. The main component of the aforementioned lattice-shaped protrusions is metal oxide, mixed with two or more different spacings. The manufacturing method of the inorganic wavelength plate includes the following steps: Polymer lattice formation process: Using a physical guiding device, a polymer having repeating units containing carbonyl groups is arranged into a lattice extending in a predetermined direction on at least one side of the transparent substrate through the self-assembly of the polymer, thereby forming a polymer lattice. Metal oxide precursor contact process: The vapor of the metal oxide precursor is brought into contact with the polymer lattice, thereby combining the metal of the metal oxide precursor with the carbonyl group to form a metal oxide precursor bonding portion; Oxidation process: Water vapor is brought into contact with the lattice having the aforementioned metal oxide precursor bonding portion, thereby oxidizing the aforementioned metal oxide precursor bonding portion to form a metal oxide lattice with metal oxide as the main component; and Etching process: Etching is performed using the aforementioned metal oxide lattice as a mask.

2. The method for manufacturing the inorganic wavelength plate according to claim 1, wherein, The above-mentioned metal oxide precursor contact process and oxidation process are repeated multiple times.

3. The method for manufacturing the inorganic wavelength plate according to claim 1 or 2, wherein, The repeating unit containing the carbonyl group mentioned above is a unit derived from methyl methacrylate.

4. The method for manufacturing the inorganic wavelength plate according to claim 3, wherein, The polymer described above, which has repeating units containing carbonyl groups, is a block copolymer comprising molecular chains of polymethyl methacrylate and molecular chains of polystyrene.

5. The method for manufacturing the inorganic wavelength plate according to claim 4, wherein the physical guiding device comprises methyl methacrylate-styrene random copolymer.

Citation Information

Patent Citations

  • 1 / 4-wavelength plate, circular polarizing plate, and liquid crystal display device

    JP1999231132A

  • Wideband 1 / 4 wavelength plate

    JP2013200908A